Comparative Efficacy of Compost, Compost Tea, Poultry Litter and Bavistin in Controlling Diseases of Chili (Progressive Agriculture, 2014)
Compost, compost tea and poultry litter in comparison with Bavistin were evaluated for controlling diseases of chili. The experiments were conducted at Field Lab. and Eco-friendly Plant Disease Management Lab. of the Department of Plant Pathology, Bangladesh Agricultural University, Mymensingh, Bangladesh in 2011- 2012 using eight different treatments following Randomized Complete Block Design with three replications. The treatments were (1) Compost tea (1 : 5 w/v) as foliar spray, (2) Soil drenching with Compost tea (1 : 5 w/v), (3) Soil drenching with poultry litter extract (1 : 5 w/v), (4) Bavistin (0.1%) as foliar spray, (5) Soil drenching with Bavistin (0.1%), (6) Compost (10 t/ha) in soil application, (7) Poultry litter (10 t/ha) in soil application and (8) control. Minimum leaf curl incidence (80.89%) and severity grade (2) were recorded in plots under Compost tea @ 1:5 w/v as foliar spray, but severity and severity grade were maximum by 95.00% and 3, respectively under control plots. Minimum anthracnose infected plants (16.67%) and infected fruit (9.35%) were recorded in plots under Compost @ 10 t/ha in soil application and soil drenching with poultry litter extract (1.5 w/v). The highest Cercospora leaf spot having severity rating grade 3.15 was recorded in field where compost tea was applied as soil drenching and lowest grade 1.07 was determined where Bavistin was applied as foliar spray. The fruit yield (4.67 t/ha) was found significantly higher in plots under compost tea as foliar spray and Bavistin as foliar spray which was 79.62% higher yield over control. Physical and chemical compositions of compost tea and poultry litter were determined.DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19096 Progress. Agric. 24(1&2): 39 - 44, 2013